2009
DOI: 10.1108/13639510911000803
|View full text |Cite
|
Sign up to set email alerts
|

Chinese police cadets' attitudes toward police role and work

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 47 publications
8
48
2
Order By: Relevance
“…However, we also find studies which conclude that the importance of previous educational attainment on the recruits' attitudes toward police role and work are limited (Sun et al, 2009), and that it does not influence the probability of arrest or search (Rydberg and Terrill, 2010). All in all, the conclusion shared by Wimshurst and Ransley (2007) and Sun et al (2009) seems reasonable: The question of whether higher education really matters for the type of police officers we get, is still not settled.…”
Section: Previous Researchmentioning
confidence: 92%
See 3 more Smart Citations
“…However, we also find studies which conclude that the importance of previous educational attainment on the recruits' attitudes toward police role and work are limited (Sun et al, 2009), and that it does not influence the probability of arrest or search (Rydberg and Terrill, 2010). All in all, the conclusion shared by Wimshurst and Ransley (2007) and Sun et al (2009) seems reasonable: The question of whether higher education really matters for the type of police officers we get, is still not settled.…”
Section: Previous Researchmentioning
confidence: 92%
“…Exceptions include Sparger and Giacopassi (1986), who find that the class background of police officers does affect their attitudes towards the wealthy, and Morash et al (2006) who includes class background as a control variable and finds that it does not have a significant effect on the self-reported occupational stress of police officers. Finally, Sun et al(2009) have found that the socio-economic status of the family does not influence the recruits' views on what are the most important tasks of the police. However, their results show that compared to the other recruits, those who have a family member working in the police see law enforcement as somewhat less important.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…However, neither of these studies explores the effect of background characteristics such as sex and level of education, or that of contextual variables such as type of duty or precinct size. All in all, this leads Sun et al (2009) to underscore the need for longitudinal studies focusing on factors influencing officers' occupational attitudes.…”
Section: Introductionmentioning
confidence: 99%